Supplementary Figure 11 from Clinicopathologic, Genomic, and Immunophenotypic Landscape of ATM Mutations in Non–Small Cell Lung Cancer - Biagio Ricciuti (14951247) (2025)
Supplementary Figure 11. Overall survival since the date of initial diagnosis among patients with stage IV NSCLC according to ATM mutation status.